(untitled) (Nigerian Dental Journal, 2025)
Objectives: Dental decay and associated toothache infection causes pains and discomfort; and are characterized by many symptoms. It may be due to bacterial infection or many other causes. This study determined the antimicrobial activities of methanol extracts of three selected Yoruba chewing sticks; Sorindeia warneckei, Garcinia kola, Veronia amygdalina and aqueous extracts of three branded toothpastes; NCT, MCL, and OLV on isolates of bacteria from cases of toothache infection Materials and Methods: A total number of thirty (30), comprising three different species, biochemically characterized isolates from tooth ache infection; Streptococcus oralis (10), Lactobacillus spp(10) and Streptococcus mutans(10) were collected on slant from a dental clinic in Ibadan and confirmed on Sheep blood agar medium fortified with serum, and deMan Rogosa Sharpe (MRS agar). The isolates were Gram stained, with other biochemical identification tests. The isolates were challenged with methanol extract of selected chewing sticks and aqueous extract of branded toothpastes using standard broth dilution method to determine its MIC’s and MBC’s. The chewing sticks extract were screened for secondary metabolites using standard methods. Results: The percentage crude extract yield from initial weight of 200g of Sorindeia warneckei was found to be 9. 25%, while Garcinia kola and Veronia amygdalina exhibited 6.8% and 5.7% Alkaloids, anthraquinones, tannins, flavonoids and saponins were present in 3 selected chewing sticks . Statistical analysis by Anova test of MIC and MBC methanol extracts for different concentrations of 3 chewing sticks and branded toothpastes evaluated showed significant inhibition of growth for 3.125, 12.56, 25 µg/mL as indicated in S.oralis1, Lactobacilli spp15 and S.mutans 30 for Sorindeia warneckei, 6.25, 3.125,6.25 µg/mL for Garcinia kola and 25, 12.5,25 µg/mL for Veronia amygdalina and when compared to 12.56 and 100 µg/mL MIC aqueous extract of 3 branded tooth pastes. The aqueous extract of toothpastes determined showed lesser antimicrobial activity than the methanol extract of the three chewing sticks from the MIC’s and MBC’s point of view. Conclusion: The methanol extract of selected chewing sticks explored showed competitive antimicrobial activity in comparison with branded toothpaste. The antimicrobial constituents in the methanol extracts of the selected chewing sticks hold the potential for clinical application and can be incorporated into conventional household tooth pastes.